PENGARUH KUALITAS PELAYANAN, HARGA, DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PADA PENGGUNA APLIKASI GO-FOOD DI KOTA JAKARTA: Bahasa Indonesia - Marthdilla Setyarana (MANAJEMEN DEWANTARA, 2022)
The purpose of this study is to analyze the impact of Service Quality, Price, Promotion on Customer Loyalty to Go-Food application users. Data was obtained by distributing online questionnaires to individuals who had used the Go-Food application. The number of samples is 102 respondents and the sampling technique used is purposive sampling. The analytical tool used is a structural equation model (SEM) with a combination of AMOS software. The results showed that there was an effect of Service Quality on Customer Loyalty of Go-Food application users. There is an effect of Price on Customer Loyalty of Go-Food application users. There is an effect of promotion on customer loyalty of Go-Food application users.